2009
DOI: 10.1111/igc.0b013e3181a1a297
|View full text |Cite
|
Sign up to set email alerts
|

Conization Using Electrosurgical Conization and Cold Coagulation for International Federation of Gynecology and Obstetrics Stage IA1 Squamous Cell Carcinomas of the Uterine Cervix

Abstract: These results suggest that electrosurgical conization with cold coagulation is a feasible treatment and could be used as a definitive therapy for patients with stage IA1 cervical squamous cell carcinoma without lymphovascular space invasion. In addition, patients having cervical intraepithelial neoplasias 2 and 3 at exocervical resection margins could be followed up carefully without further treatment after conization and cold coagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Then, the electrosurgical conization was performed by using a right-angled triangular loop, carrying a high frequency current which can penetrate tissue more deeply toward the uterine endocervix than the conventional round loop. 5 Thereafter, a cold coagulator (120 o C) was applied to the cone bed for 30-60 seconds after excision for the purpose of hemostasis and destruction of any residual lesion after electrosurgical excision. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the electrosurgical conization was performed by using a right-angled triangular loop, carrying a high frequency current which can penetrate tissue more deeply toward the uterine endocervix than the conventional round loop. 5 Thereafter, a cold coagulator (120 o C) was applied to the cone bed for 30-60 seconds after excision for the purpose of hemostasis and destruction of any residual lesion after electrosurgical excision. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In the past, radical methods have been applied to cases of cervical carcinoma stage IA1 [5,6]. There is, however, an obvious move toward a conservative approach, where simple hysterectomy is the method of choice, although conization is a feasible treatment for patients who desire to preserve their fertility [7].…”
Section: Introductionmentioning
confidence: 99%
“…Given the excellent prognosis of patients with stage IA1 cervical cancer, fertility-conserving therapy with conization has been proposed as an alternative to hysterectomy for young women. [2][3][4][5][6][7][8][9][10] Although small institutional series and case control studies have suggested that conization is safe, large studies comparing conization and hysterectomy for stage IA1 cervical cancer are largely lacking. The objective of our study was to examine the safety of fertility-conserving conization in a large cohort of young women with stage IA1 squamous cell carcinoma of the cervix.…”
mentioning
confidence: 99%